Freedom, equality, and the market : arguments on social policy - Hindess, Barry (Social science paperbacks ;, 1987)
This new textbook for students of social theory considers the role of public intervention in social and economic processes. It is a clear, critical discussion of different theoretical and political perspectives on social policy. Freedom, Equality, and the Market, with its careful assessment of the key texts, will be important reading for undergraduate students of sociology and social policy.